2006
DOI: 10.1158/1535-7163.mct-05-0347
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone suppresses human lung carcinoma cell growth through PPARγ-dependent and PPARγ-independent signal pathways

Abstract: Peroxisome proliferator-activated receptors ; (PPAR;) exert diverse effects on cancer cells. Recent studies showed that rosiglitazone, a synthetic ligand for PPAR;, inhibits cell growth. However, the exact mechanisms underlying this effect are still being explored, and the relevance of these findings to lung cancer remains unclear. Here, we report that rosiglitazone reduced the phosphorylation of Akt and increased phosphatase and tensin homologue (PTEN) protein expression in nonsmall cell lung carcinoma (NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 46 publications
9
135
0
3
Order By: Relevance
“…Subsequently, we found that rosiglitazone enhanced 5-FU-inhibited cell growth of HCC via PPARγ activation, because the effect was completely abrogated by the inactivation of PPARγ through PPARγ siRNA. Han et al have demonstrated that rosiglitazone inhibits nonsmall cell lung cancer (NSCLC) cell growth by both PPARγ-dependent and PPARγ-independent signaling pathways [28] . Our results show that rosiglitazone increases the antitumor effect of 5-FU via the PPARγ-dependent signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we found that rosiglitazone enhanced 5-FU-inhibited cell growth of HCC via PPARγ activation, because the effect was completely abrogated by the inactivation of PPARγ through PPARγ siRNA. Han et al have demonstrated that rosiglitazone inhibits nonsmall cell lung cancer (NSCLC) cell growth by both PPARγ-dependent and PPARγ-independent signaling pathways [28] . Our results show that rosiglitazone increases the antitumor effect of 5-FU via the PPARγ-dependent signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, rosiglitazone inhibits NSCLC cell proliferation through PPARγ-dependent signals. 54 However, it also occurs by PPARγ-independent signals, as increase in the phosphorylation of AMPKα, which is mediated by rosiglitazone, is not affected by treatment with PPARγ antagonist, GW9662. 54 Recently, Chaffer et al 75 have demonstrated that both PPARγ agonists, TGZ and 15dPGJ2, inhibited prostate and bladder cancer cell growth in a PPARγ-independent fashion.…”
Section: Role In Cancer Biologymentioning
confidence: 99%
“…54 However, it also occurs by PPARγ-independent signals, as increase in the phosphorylation of AMPKα, which is mediated by rosiglitazone, is not affected by treatment with PPARγ antagonist, GW9662. 54 Recently, Chaffer et al 75 have demonstrated that both PPARγ agonists, TGZ and 15dPGJ2, inhibited prostate and bladder cancer cell growth in a PPARγ-independent fashion. These findings suggest that these anti-tumor effects induced by the PPARγ agonists are attributed to regulation of other various cellular signaling pathways, independently from the PPARγ receptor pathways.…”
Section: Role In Cancer Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…31,[46][47][48] Although the critical mechanisms responsible for biological activity of these ligands are not known, one recent study has shown that rosiglitazone can activate AMP dependent kinase in NSCLC cells in a PPARγ independent manner, which decreases cellular proliferation through inhibition of mTOR. 50 Because mTOR is a kinase downstream of Akt that promotes cellular proliferation and survival, it is possible that the effectiveness of combining PPARγ ligands with TRAIL lies in modulation of multiple pathways that control cellular survival and cell death. The mechanism by which this might occur is a key area that needs to be explored further since this is likely to unveil interesting and important molecular mechanisms modulated by the PPARγ ligands.…”
mentioning
confidence: 99%